Moo Ya: The Spirit of the River - Ticozzi, Filippo (Italy, 2016)
The main protagonist of the documentary is a blind man who lives in a remote village in Uganda, Africa. One day he decides to travel and camera is following his journey.
Keywords: Documentary films